Bulky α-diimine palladium complexes: highly efficient for direct C–H bond arylation of heteroarenes under aerobic conditions. Issue 38 (18th August 2016) - Ouyang, Jia-Sheng; Li, Yan-Fang; Shen, Dong-Sheng; Ke, Zhuofeng; Liu, Feng-Shou
Abstract : Through the strategy to enhance the bulkiness on both the backbone and the N -aryl moieties, we designed and synthesized a type of bulky α-diimine palladium complex ( i.e., [Ar–N{C(R)–C(R){N–Ar]PdCl2, (Ar = 2-benzhydryl-4, 6-dimethylphenyl), C1, R = H;C2, R = An;C3, R = Ph). Abstract : Through the strategy to enhance the bulkiness on both the backbone and the N -aryl moieties, we designed and synthesized a type of bulky α-diimine palladium complex ( i.e., [Ar–N{C(R)–C(R){N–Ar]PdCl2, (Ar = 2-benzhydryl-4, 6-dimethylphenyl), C1, R = H;C2, R = An;C3, R = Ph). The structures of these palladium complexes were well characterized, whileC1 andC3 were further characterized by X-ray diffraction. The catalytic performances of the precatalysts were screened for direct C–H bond arylation of heteroarenes. The bidentate N, N -palladium complexC3 with both a backbone and N -aryl bulkiness was found to be a highly efficient precatalyst under aerobic conditions. With a low palladium loading of 0.5–0.1 mol%, a variety of heteroarenes with challenging bulky steric aryl bromides as well as heteroaryl bromides are all applicable for this cross-coupling reaction.